2023
DOI: 10.1164/rccm.202206-1084oc
|View full text |Cite
|
Sign up to set email alerts
|

The Biological Role of Pleural Fluid PAI-1 and Sonographic Septations in Pleural Infection: Analysis of a Prospectively Collected Clinical Outcome Study

Abstract: Contributor statementEOB, NIK and NMR conceived and designed the study. JPC and EOB curated the PILOT database. EOB, NIK and YZ performed the laboratory processing and analyses. EOB and NMR analysed the data. MH, RA, RMM, AS and DNA contributed clinical data. EOB wrote the first draft of the manuscript. TD provided materials. RFM, TD and AMC provided expert knowledge. All authors reviewed and approved the final manuscript. EOB, NIK and NMR verified the underlying data and jointly act as guarantors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Chen and colleagues found in retrospective data sets that the presence of septation on ultrasound imaging appeared to predict the need for chest tube drainage and intrapleural enzyme treatment and correlated negatively with survival ( 7 , 8 ). The survival link was not demonstrated in the PILOT study, however, or in a recent prospective study by Bedawi and colleagues, with septations predicting longer hospital stay only ( 9 ). Few reliable data exist on computed tomography (CT) imaging and the features of empyema that may predict outcome and overall prognosis.…”
mentioning
confidence: 84%
“…Chen and colleagues found in retrospective data sets that the presence of septation on ultrasound imaging appeared to predict the need for chest tube drainage and intrapleural enzyme treatment and correlated negatively with survival ( 7 , 8 ). The survival link was not demonstrated in the PILOT study, however, or in a recent prospective study by Bedawi and colleagues, with septations predicting longer hospital stay only ( 9 ). Few reliable data exist on computed tomography (CT) imaging and the features of empyema that may predict outcome and overall prognosis.…”
mentioning
confidence: 84%
“…82 Furthermore, elevated levels of PAI-1, the major inhibitor of fibrinolysis in the inflamed/infected pleural space, appear to be associated with the development of septations and their severity, length of hospital stay, and mortality. 83 PAI-1 is known to inhibit the activity of uPA and t-PA; it is possible that levels of PAI-1 rise over time and reduce the efficacy of intrapleural enzyme therapy (IET). 84 In the future, it may be that baseline levels of PAI-1 could be used to guide the need for drainage, the procedure chosen, and choice and dose of fibrinolytic agents (see below).…”
Section: Pathogenesismentioning
confidence: 99%
“…731–739) in the Journal on the biological role of pleural fluid plasminogen activator inhibitor (PAI)-1 and sonographic septations in pleural infection ( 1 ). The study showed that the pleural fluid PAI-1 concentration is significantly associated with the presence and severity of sonographic septation, length of hospital stay, and 12-month mortality in patients with pleural infection ( 1 ). These results are consistent with previous studies showing the detrimental effect of PAI-1 in pleural injury ( 2 , 3 ).…”
mentioning
confidence: 99%
“…The uPA/PAI-1 ratio is a good indicator of the balance between pro- and antifibrinolysis ( 6 ). Bedawi and colleagues measured the pleural fluid concentration of uPA and found no significant correlation of the pleural fluid concentration of uPA with sonographic septation status, septation severity, or mortality ( 1 ). However, they did not evaluate the fibrinolytic status by calculating the uPA/PAI-1 ratio.…”
mentioning
confidence: 99%